To speak or not to speak in the new Taiwanese university: class participation and identity construction in linguistically and culturally diverse graduate classrooms. (4th March 2018) - Lin, Shumin
ABSTRACT: In order to internationalize higher education, universities across Asia have engaged in aggressive recruitment of international students and increased provision of English-medium instruction (EMI). While many studies have examined Asian international students' intercultural interactions during class discussions in Western/English-speaking countries, little is known about how the diverse students interact in EMI classes in the newly internationalized universities in Asia. This study analyzed interviews with 82 graduate students in a Taiwanese university to examine their classroom participation and identity construction in EMI. Findings indicate that Taiwanese and international students diverge in their frequency, manner, and content of speech in whole class discussions. Students explained the contrast in terms of cultural and linguistic identities while they also reported a dynamic two-way adjustment in their classroom behaviors over time. Previous studies emphasized the need for context-oriented analysis of students' intercultural classroom experiences and tended to focus on the classroom contexts. This study suggests that such contextualized analysis needs to also attend to the local linguistic contexts and power relations between languages and cultures as they are intertwined with the cultural and linguistic identity construction that influence classroom behaviors in the non-Western and non-native-English-speaking settings.